Keamanan Sistem Informasi Rekam Medis Elektronik Di Rumah Sakit Islam Jakarta Sukapura - Endah Wardani; Daniel Happy Putra; Dina Sonia; Noor Yulia (Indonesian Journal Publisher, 2024)
The implementation of Electronic Medical Records (EMR) in all health service facilities is outlined in Minister of Health Regulation Number 24 of 2022, with a deadline of 31 December 2023. Ensuring the security of EMR is vital to protect patient data privacy, prevent unauthorized data access, and avoid breaches. This study evaluates the security practices of EMR systems at the Islamic Hospital Jakarta Sukapura using a descriptive qualitative research method with seven informants. The study focuses on six key aspects of EMR security: privacy, integrity, authentication, availability, access control, and non-repudiation. The results show that the hospital has established security procedures, such as using usernames and passwords, but there are significant areas for improvement. The study notes the need for automatic logout features to prevent unauthorized access when computer screens are left unattended and emphasizes the importance of regularly updating passwords to improve security, as well as hospitals using encryption and firewall technologies to protect data during transmission and storage. Apart from this, research shows that some staff members still use default passwords, posing a security risk. Overall, this study provides recommendations for strengthening RME security frameworks in hospitals.